2003
DOI: 10.1161/01.str.0000050644.48393.d0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy in Acute Ischemic Stroke

Abstract: Background and Purpose-Hyperbaric oxygen therapy (HBO) has promise as a treatment for acute stroke. This study was conducted to evaluate the efficacy, safety, and feasibility of using HBO in acute ischemic stroke. Methods-We conducted a randomized, prospective, double-blind, sham-controlled pilot study of 33 patients presenting with acute ischemic stroke who did not receive thrombolytics over a 24-month period. Patients were randomized to treatment for 60 minutes in a monoplace hyperbaric chamber pressurized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(75 citation statements)
references
References 19 publications
3
71
0
1
Order By: Relevance
“…There is accumulating evidence indicating that oxygen therapy is safe and feasible (Rusyniak et al, 2003), and may be neuroprotective for acute ischemic stroke (Singhal et al 2002b). Experiments by Singhal et al (2002a;2002b) showed that normobaric hyperoxia during focal cerebral ischemia-reperfusion salvaged ischemic brain tissue, with no increased oxidative stress being found to result from this hyperoxia treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is accumulating evidence indicating that oxygen therapy is safe and feasible (Rusyniak et al, 2003), and may be neuroprotective for acute ischemic stroke (Singhal et al 2002b). Experiments by Singhal et al (2002a;2002b) showed that normobaric hyperoxia during focal cerebral ischemia-reperfusion salvaged ischemic brain tissue, with no increased oxidative stress being found to result from this hyperoxia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Determining these interstitial oxygenation changes in penumbra and core are therefore crucial to fully understanding the processes occurring in the penumbra. Furthermore, monitoring interstitial oxygenation will provide accurate values for evaluating emerging hyperbaric (Rusyniak et al, 2003) and normobaric (Singhal et al, 2002a;2002b) oxygen therapies in acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…14) However, previous randomized controlled human studies of HBO therapy have demonstrated no benefit, 3,15,20) and the American Stroke Association guidelines for the early management of patients with ischemic stroke suggest that the evidence does not support the general use of HBO therapy in patients with acute ischemic stroke. 2) Precisely why our combined treatment achieved a favorable clinical outcome is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, patients with various ischemic stroke subtypes were included in the group treated unsuccessfully with HBO, 3,15,20) whereas we studied only patients with embolic stroke. As about 40% of occluded arteries recanalize spontaneously within a few days after the embolic stroke onset, 9) HBO may minimize brain damage adjunctively 8,10) by maintaining the viability of the ischemic penumbra until spontaneous recanalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation